Micromechanical models for fabrics and composites made of hybrid yarns from recycled carbon fibers - Lang, Tobias; Hasan, Mir Mohammad Badrul; Huynh, Thy Anh My; Gereke, Thomas; Abdkader, Anwar; Cherif, Chokri (Wydawnictwo Politechniki Łódzkiej, 2022)
Although the great potential of carbon fibers for use in lightweight applications has been demonstrated in the past, their cost and environmental impact remain a barrier to their widespread use [1]. Recycling of carbon fibers from end-of-life components and combining them with thermoplastic fibers to form hybrid yarns addresses both issues. Due to the stochastic nature of hybrid yarns in terms of recycled carbon fiber (rCF) length and orientation [2], their influence on drapability and performance of rCF composites needs to be investigated. In this paper, a micromechanical model for analysing the dry and composite properties of yarns made from rCF is presented. By using a self-developed framework for generating representative volume elements (RVE) based on parameters such as fiber length, orientation, waviness, and fiber volume content, a variety of idealised random yarn geometries is created. A subsequent simulation step of the compaction of the RVE assures a more realistic RVE geometry. The models are validated by carrying out virtual tests and comparing the results with real tensile tests. The modelling approach can be used for further analyses.
Keywords: finite element method; hybrid yarns; micromechanical model; recycling carbon fibers; metoda elementów skończonych; przędze hybrydowe; model mikromechaniczny; recykling włókien węglowych